2008
DOI: 10.1007/s10708-008-9152-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative urbanization in Ghana and Kenya in time and space

Abstract: There are few inter-African country urban analyses because of the continent's enormous size and socioeconomic diversity, language barriers, and wide variations in national and regional urban research capacity. Nevertheless, comparative urban studies are critical in understanding contemporary African urbanization. In this comparative spatial and temporal analysis of Ghana and Kenya's urbanization, we find that both countries are urbanizing rapidly and are faced with many common urban problems. Moreover, Ghana i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 25 publications
(51 reference statements)
0
37
0
Order By: Relevance
“…Early Pre and Post-colonial urbanisation in Kenya acted to disenfranchise urban citizens and consequently denied them the right to the city (Otiso and Owusu 2008). Colonialism in Kenya was one of the key precipitous of urbanisation.…”
Section: Colonialism Urban Disenfranchisement and Right To The City mentioning
confidence: 99%
See 2 more Smart Citations
“…Early Pre and Post-colonial urbanisation in Kenya acted to disenfranchise urban citizens and consequently denied them the right to the city (Otiso and Owusu 2008). Colonialism in Kenya was one of the key precipitous of urbanisation.…”
Section: Colonialism Urban Disenfranchisement and Right To The City mentioning
confidence: 99%
“…The few Africans who were allowed in the city served as labourers in construction of the railway, roads, home guards, cooks, maids and other unskilled jobs for white settlers. As opposed to their white counterparts, they were housed in segregated camps and urban reserves (Otiso and Owusu 2008). (Morgan 1969) notes, ''Migration into towns is subject to both a 'pull' and a'push'.…”
Section: Colonialism Urban Disenfranchisement and Right To The City mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, improved transport and communication connections with the outside world, coupled with economic difficulties in many African countries forced many of their nationals to relocate to other global destinations in search of better socioeconomic opportunities. These transnational émigrés, coupled with the heightened expansion of many global corporations into Africa and the continent's improved transport and communications with the outside world in the global era, have contributed to the rapid globalization of many African cities since the 1980s (Otiso and Owusu 2008). Nevertheless, the globalization of African cities in the recent past is far from uniform as emerging studies of globalizing African cities such as Accra, Nairobi, and Johannesburg have shown (Grant 2009, Otiso and Owusu 2008, Robinson 2006.…”
Section: Introductionmentioning
confidence: 99%
“…These transnational émigrés, coupled with the heightened expansion of many global corporations into Africa and the continent's improved transport and communications with the outside world in the global era, have contributed to the rapid globalization of many African cities since the 1980s (Otiso and Owusu 2008). Nevertheless, the globalization of African cities in the recent past is far from uniform as emerging studies of globalizing African cities such as Accra, Nairobi, and Johannesburg have shown (Grant 2009, Otiso and Owusu 2008, Robinson 2006. In spite of these recent studies, however, the globalization of many African cities remains poorly understood because of the rather limited scholarly attention (with notable exceptions being Rakodi 1998, Van der Merwe 2004, Pirie 2010, and Grant 2009, largely because the continent is seen as being marginal to the global economy and, therefore, devoid of the so-called 'global cities' that are "the sites for the control and management of TNC [Transnational Corporation] operations, specialized business services to back these up, and nodes in the world banking and commercial system" (Rakodi 1998: 329-330) 1 .…”
Section: Introductionmentioning
confidence: 99%